2016
DOI: 10.3390/nu8050283
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn Fruit Extract Elevates Expression of Nrf2/HO-1 and Improves Lipid Profiles in Ovariectomized Rats

Abstract: The purpose of this study was to investigate the effects of hawthorn (Crataegus pinnatifida Bunge) extract on the lipid profiles and antioxidant properties in ovariectomized (OVX) rats. After ovariectomy, the rats were randomly divided into four groups: the non-OVX control (Sham), the OVX-control (OVX), the OVX + 100 mg/kg b.w. of hawthorn extract (OL), and the OVX + 200 mg/kg b.w. of hawthorn extract (OH). The final body weights of the OVX group were significantly increased, but the increment was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 69 publications
2
28
0
1
Order By: Relevance
“…Numerous studies have demonstrated that antioxidants showed antioxidative activity not only by directly scavenging intracellular ROS, but also by fortifying cellular antioxidant defense system. In this regard, antioxidant and detoxifying enzymes, such as glutathione peroxidase (GSH-Px), catalase (CAT), heme oxygenase (HO-1), NAD(P)H:quinone oxidoreductase I (NQO1) and glutathione S -transferase (GST), are important parts of the system [ 32 ]. Whey protein hydrolysate mitigated the paracetamol-induced oxidative damage by increasing the total antioxidant potential of hepatocytes and activities of antioxidant enzymes in mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that antioxidants showed antioxidative activity not only by directly scavenging intracellular ROS, but also by fortifying cellular antioxidant defense system. In this regard, antioxidant and detoxifying enzymes, such as glutathione peroxidase (GSH-Px), catalase (CAT), heme oxygenase (HO-1), NAD(P)H:quinone oxidoreductase I (NQO1) and glutathione S -transferase (GST), are important parts of the system [ 32 ]. Whey protein hydrolysate mitigated the paracetamol-induced oxidative damage by increasing the total antioxidant potential of hepatocytes and activities of antioxidant enzymes in mice [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…C. pinnatifida extract decreased the levels of serum TC, LDLC, hepatic TG and MDA, increased mRNA expression of nuclear erythroid 2-related factor (Nrf2), heme oxygenase-1 (HO-1), Gpx and reversed the suppression of protein levels in ovariectomized rats (Yoo et al, 2016). reported that C. pinnatifida HLF ameliorated hepatic steatosis by enhancing the adiponectin/ AMPK pathway in the liver of HFD-induced NAFLD rats.…”
Section: Hypolipidemic Effectsmentioning
confidence: 96%
“…The determination of malondialdehyde (MDA) by thiobarbituric acid (TBA) was used as an index of the extent of lipid peroxidation [21,22]. Briefly, 0.1 g of stomach tissue was homogenized using 1 mL of 1.15% potassium chloride (Sigma-Aldrich, Co., St. Louis, MO, USA) followed by successive additions of 0.2 mL of 8.1% sodium dodecyl sulfate solution (SDS) (IBS-BS003a; iNtRON Biotechnology, Gyeonggi-do, Korea), 1.5 mL of 20% acetic acid (Daejung Chemical, Suwon, Korea), 1.5 mL of 0.8% aqueous TBA (Sigma-Aldrich, Co., St. Louis, MO, USA), and 0.7 mL of distilled water.…”
Section: Measurement Of Gastric Peroxidationmentioning
confidence: 99%